2016
DOI: 10.4103/0974-2069.189119
|View full text |Cite
|
Sign up to set email alerts
|

Profile and risk factors for congenital heart defects: A study in a tertiary care hospital

Abstract: Introduction:Congenital heart defects (CHDs) are an important cause of mortality and morbidity in children representing a major global health burden. It is thus important to determine their prevalence and spectrum and identify risk factors associated with the development of heart defects.Materials and Methods:A case-control study was carried out in the Department of Pediatrics and Center of Cardiology, Jawaharlal Nehru Medical College, Aligarh Muslim University, Aligarh, Uttar Pradesh, India, from February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
38
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 14 publications
(18 reference statements)
14
38
3
5
Order By: Relevance
“…4,5 The prevalence of congenital heart disease was found to be 5.8/1000 hospitalized patients by Shah GS et al, 13.28% by Sawant SP et al conducted at Mumbai whereas in the present study it was 6.49%. 5,6 Acyanotic heart disease constituted 27.50% of the congenital heart disease according to Abquari S. 4 In the present study the prevalence was found to be 13.69%. A study by Shah GS estimated the prevalence of cyanotic congenital heart disease to be 31%.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…4,5 The prevalence of congenital heart disease was found to be 5.8/1000 hospitalized patients by Shah GS et al, 13.28% by Sawant SP et al conducted at Mumbai whereas in the present study it was 6.49%. 5,6 Acyanotic heart disease constituted 27.50% of the congenital heart disease according to Abquari S. 4 In the present study the prevalence was found to be 13.69%. A study by Shah GS estimated the prevalence of cyanotic congenital heart disease to be 31%.…”
Section: Discussioncontrasting
confidence: 49%
“…The prevalence of congenital diaphragmatic hernia in this study was found to be 2.66/10000 live births, whereas that in a study done by Burgos CM et al in Sweden, it was found to be 3.5/10000 deliveries, and in a study done by Grizelj R et al in Croatia it was found to be 2.67/10000 live births. 4,10 In this study the prevalence of structural congenital anomalies at the time of birth before discharge were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…9 We have also observed an increase in the number of ASD (16.88%) as the second common CHD. This may be attributable to over-diagnosis of patent foramen ovale as atrial septal defect.…”
Section: Discussionmentioning
confidence: 57%
“…9 Some studies shows the male preponderance of 2.08:1 and 1.78:1 but we didn't get a significant gender disparity (1.2:1). 10,11 This small disparity may be explained on basis of social issue in our country, which may be due to high health seeking behaviour in parents for male child.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 31 studies published between 1990 and 2018 according to the inclusion criteria. Study selection was summarized in Figure .…”
Section: Resultsmentioning
confidence: 99%